Development of Studentsâ Worksheet with Realistic Mathematic Education on Subject Triangel - Atika, Nur; MZ, Zubaidah Amir (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The research aims to produce studentsâ worksheet validly and practically with Realistic Mathematic Education (RME) approach on the triangle lesson. This research was conducted at Junior High School 7 Bengkalis. The subject of this research are the experts and students class VII which 6 among them taken as small group trial and 30 students taken as big group trial. The development usedthe ADDIE method, namely: (A) analysis, including the curriculum analysis and the needs analysis; (D) design, including the preparation of studentsâ worksheet; (D) development, to develop studentsâ worksheet with Realistic Mathematics Education (RME); (I) implementation, in the small and big group; (E) evaluation, to analyze the data. The scores of results through the inquiry conducted by the media, the material, the small group trial, and the big group trialare90%,84,45%,90,08%, and 89,14% respectively. The data shows that the development of the studentsâ worksheet is appropriate and does not have to be revised, but needs to follow up on comments and suggestions to complete.